Jazz A-B-Z - Marsalis, Wynton 1961- (Candlewick Press, 2005)
Profiles twenty-six of the jazz greats of all time, from Count Basie to Louis Armstrong, through a review of their work, their life stories, and their greatest hits by one of today's top jazz performers. A is for "almighty" Louis Armstrong, whose amazing artistry unfolds in an accumulative poem shaped like the letter he stands for. As for sax master Sonny Rollins, whose "robust style radiates roundness," could there be a better tribute than a poetic rondeau? In an extraordinary feat, Pulitzer Prize-winning jazz composer Wynton Marsalis harmonizes his love and knowledge of jazz's most celebrated artists with an astounding diversity of poetic forms-from simple blues (Count Basie) to a complex pantoum (Charlie Parker), from a tender sonnet (Sarah Vaughan) to a performance poem snapping the rhythms of Art Blakey to life